Knowledge Gap about Organic Farming Practices of Farmers of Bageshwar District of Uttarakhand - Sahu, R.P.; Singh, Raman Jeet; Singh, Khilendra (Indian Journal of Extension Education, 2010)
Organic farming is not new to our country. For almost the last fifty years indian agricultural practices have mainly concentrated on increasing yield, leading to cultivation of mono crops. This in turn has made the crops highly vulnerable to pest attacks, soil becoming barren and ground water, toxic. In addition, the raising input cost and fertilizer shortage have made farmers try organic methods as an alternative to chemical farming.